Graphene oxide as a multifunctional synergist of insecticides against lepidopteran insect. Issue 1 (12th December 2018) - Wang, Xiuping; Xie, Haicui; Wang, Zhenying; He, Kanglai; Jing, Dapeng
Abstract : GO can cause "physical damage" to the cuticle that provides a new channel for the penetration of insecticides. Abstract : Application of nanotechnology in plant protection via formulating nanomaterial-based pesticides to improve pesticide bioactivity has attracted significant research interest in recent years. In this study, the synergistic activity and mode of GO for insecticides against a lepidoptera insect Asian corn borer (ACB) were investigated. The results demonstrated excellent synergistic activities of GO for the three types of insecticides, namely, β-cyfluthrin (Cyf), Monosultap (Mon) and Imidacloprid (Imi). GO–Cyf, GO–Mon and GO–Imi mixtures exhibited 2.1-, 1.51- and 1.83-fold higher contact toxicities than the individual insecticides of Cyf, Mon and Imi, respectively. Our results indicated that the synergistic mechanism may involve the following phenomena: (i) GO can cause 'physical damage' to the cement layer of insects, resulting in rapid water loss for the insects, (ii) the disrupted cement layer provides a new channel for the penetration of insecticides, and (iii) the GO delivery system can enhance the efficacy of the insecticides. This multifunctional mechanism that allows GO to serve as a synergist for the existing insecticides demonstrates the excellent application potential of GO in pest management.